KELAYAKAN INVESTASI PEMBANGUNAN CONVENTION CENTER DI KOTA MAKASSAR - Suprawa, Tindra Adi (Fakultas Teknik Universitas 17 Agustus 1945 Surabaya, 2014)
The research was conducted to determine: (1) the value of the investment and appropriate management, (2) get the price of the room rental Convention Center and get a long time the most optimal cooperation with (3) investors Makassar City Convention Center construction using collaboration systems Build Operate Transfer (BOT). The results of this study were (1) Convention Center construction project requires investment of Rp 58.026 billion. Assuming a rate of 10% per year, it acquired the investment period of 13 years 9 months. Convention Center construction project is declared eligible to run. It can be seen from the value of NPV > 0 is Rp 4.490 billion, the value of IRR exceeds the expected interest rate is 11.58%, Break Even Point Convention Center rental business happened in year 8 over 2 months, precisely in 2021, ( 2) the optimal rental fee for each hour is Rp 6.5 million, (3) time of development cooperation with the investor Makassar Convention Center using a system of cooperation Build Operate Transfer (BOT). Based on a DPP, then the values obtained Discounted Payback Period (DPP) from businesses Convention Center is 13 years and 9 months faster than the 15-year investment period.Kata kunci: Convention Center, kelayakan, Build Operate Transfer